Using the Demirjian method for estimating the dental age of children in Surabaya, Indonesia - Beshlina Fitri Widayanti Roosyanto Prakoeswa; Arofi Kurniawan; An'nisaa Chusida; Beta Novia Rizky; Anugerah I'zaaz Darmawan; Andini Kamilia Nur Aisyah; Aspalilah Alias (Universitas Airlangga, 2023)
Background: The Demirjian method is used in assessing the stages of growth and development of teeth to calculate a person's estimated age. In 1973, Demirjian identified the eight stages of tooth growth and development and their respective criteria. Purpose: To analyze the validity of Demirjian's method for estimating dental age among children aged 6-17 years old in Surabaya, Indonesia. Methods: From August-October 2020, 162 panoramic radiographs of patients aged 6-17 years were taken at the radiology department of Airlangga Dental Hospital. Data analysis was conducted using SPSS software for different tests, including a paired t test. Results: Using the Demirjian method, there was no significant dissimilarity between chronological age (CA) and estimated dental age (EDA) in the male group. However, a significant dissimilarity was found between CA and EDA in the female group. Conclusion: Demirjian's method can be used as a tool for estimating the dental age of males age 6-17 years old in Surabaya.